Comprehensive Study on Wi-Fi Security Protocols by Analyzing WEP, WPA, and WPA2 - Khaled Ahmed Adbeib (African Journal of Advanced Pure and Applied Sciences, 2023)
This project has undertaken a thorough investigation into Wi-Fi protocols, namely Wired Equivalent Privacy (WEP), Wi-Fi Protected Access (WPA), and Wi-Fi Protected Access version 2 (WPA2). The analysis meticulously explored the encryption and decryption processes, strengths, weaknesses, and vulnerabilities inherent in each protocol. Additionally, a critical examination of common attacks associated with these protocols was conducted, elucidating the mechanisms through which these attacks can succeed. The research successfully achieved its key objectives, providing a detailed examination of WEP, WPA, and WPA2 and conducting a comprehensive evaluation of their inherent strengths and weaknesses. Furthermore, insights into the methodologies and techniques used by malicious actors to compromise network security were presented. The comparative analysis facilitated a nuanced understanding of the features and security attributes of WEP, WPA, and WPA2. Finally, the research proposed recommendations based on its findings, aiming to assist users in implementing robust security measures and mitigating potential vulnerabilities in Wi-Fi networks. This comprehensive study contributes to an enhanced understanding of Wi-Fi security protocols, empowering users to make informed decisions and advancing network security practices.